2016
DOI: 10.1021/acssensors.5b00306
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection in Serum: RNA-Cleaving DNAzymes for Measuring Ca2+ and Mg2+

Abstract: RNA-cleaving DNAzymes have been attempted as in vivo analytical probes and gene silencing reagents over the past two decades. Despite progress already achieved, concerns still exist regarding the activity of DNAzymes in biological fluids. An example is the low activity of the 10–23 DNAzyme in intracellular Mg2+ concentrations. To obtain DNAzymes that work optimally in biological samples, we herein report the first DNAzyme in vitro selection in undiluted human blood serum. The selection starts with a large DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 58 publications
0
45
0
Order By: Relevance
“…A key advantage of in vitro selection is that DNAzymes can be isolated under physiological conditions or even using biological fluids directly to ensure their activity for the intended applications 17. On the other hand, extreme conditions such as high temperature or low pH can be used for other tailored applications 18, 19.…”
Section: In Vitro Selection Of Dnazymesmentioning
confidence: 99%
See 2 more Smart Citations
“…A key advantage of in vitro selection is that DNAzymes can be isolated under physiological conditions or even using biological fluids directly to ensure their activity for the intended applications 17. On the other hand, extreme conditions such as high temperature or low pH can be used for other tailored applications 18, 19.…”
Section: In Vitro Selection Of Dnazymesmentioning
confidence: 99%
“…We reported that the 8-17 is even faster than the 10-23 for cleaving chimeric substrates in the presence of Mg 2+ 25. The 8-17 motif has been repeated selected by several labs using Zn 2+ 26, Mg 2+ 27, 28, Ca 2+ 17, 28, Cd 2+ 29, and other conditions with the best activity observed with Pb 2+ 30. Its recurrence has been attributed to the small size, high tolerance to mutations, and high activity 27.…”
Section: Some Representative Dnazymesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 17E DNAzyme is an extensively studied model enzyme, and it is active in the presence of many divalent metal ions. For this reason, together with its small size and tolerance to mutations, 17E has recurred in many in vitro selections from different labs under different selection conditions . The highest activity is achieved with Pb 2+ , followed by Zn 2+ , Cd 2+ , Mn 2+ , and Co 2+ , whereas a high metal concentration is needed for Mg 2+ and Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro selection starts with approximately 10 15 different DNA sequences and, based on the selection conditions, can produce DNAzymes which are highly specific for metal ion cofactors in a range of concentrations. Thus far, DNAzymes have been selected that are specific for Pb 2+ [6]-[8], Zn 2+ [9,10], Mg 2+ [8,11], Cu 2+ [12], Ca 2+ [13], UO2 2+ [14], Na + [15], Hg 2+ [16], Cd 2+ [17], Cr 3+ [18], Ln 3+ [19-21], Ce 3+ [22], and Ag + [23]. …”
Section: Introductionmentioning
confidence: 99%